Reduction of the Battery Capacity of Hybrid Electric Vehicle with the Help of Electrically Assisted Turbocharger - Mihaylov Milen (EDP Sciences, 2021)
In this manuscript, the reduction of the battery capacity of a hybrid electric vehicle with the help of electrically assisted turbochargers was analyzed. Using the battery for vehicle propulsion and the options for its recharging, it could be concluded, that the most efficient way would be to use the battery energy for boosting mainly through eTurboTM and recharge the battery mainly with the traction motor in regenerative braking. Based on both steady-state and transient analysis it is clear, that for having the same dynamic HEV performance, the boosting with propulsion through ICE requires significantly less energy from the battery compared to the boosting through the traction motor. Therefore using the eTurboTM as boosting device can lead to reduce the battery capacity and reduce fuel consumption and emission of the vehicle.